Chronic ventilation and social participation: experiences of men with neuromuscular disorders. (May 2013) - van Huijzen, Selma; van Staa, AnneLoes
Abstract Objective: The purpose of this study was to investigate how mechanical ventilation-dependent adults with neuromuscular disorders experience their occupational and social participation. Methods: Data were collected through two successive focus-group discussions with six men (aged 23–40 years) living in the same specialized nursing home in the Netherlands. Results: The results showed that the participants wanted to be involved in activities that provide interaction with others in society or community; they desired social participation. Thematic analysis brought out that the participants wanted to be taken seriously in all aspects of life. Four themes emerged: "Responsibility for risk-taking", "The influence of dependency", "Being treated as an employee", and "Maintaining optimism". These men appreciated good information from health care providers, wanted to have more autonomy in decision-making and risk-taking – and did not wish to be patronized. They wanted to have a social network to help them suction their tracheal cannula. Also, they would like activities at the activity centre to be more contributing to society and wished to be treated as employees rather than as clients. In view of their short life expectancy, they would also welcome discussions of end-of-life issues in group sessions led by a professional. Facilitating aspects of social participation, i.e. the experience of meaningful occupations in connection with autonomy and self-determination, would provide a more client-centred approach.